Становище осередків Української соціал-демократичної спілки на початку столипінської реакції - Федьков, О.М. (Український історичний журнал, 2017)
Висвітлюються умови, форми та методи діяльності членів осередків УСДС
в українських ґуберніях Російської імперії у другій половині 1907 – на початку
1908 рр. Використання методів дослідження соціальної історії (історії повсякдення) дозволило охарактеризувати Спілку як революційну соціал-демократичну організацію. Using methods of researching social history (history of everyday life), we characterized
the weekdays of the outstanding and ordinary figures of the Ukrainian Social-
Democratic Union at the beginning of the Stolypin reaction. The situation of Union’s
societies in the circumstances of persistent repressions and the work of secret agents
in their ranks has been clarified. It is noted that members of the Union, using conspiring
methods of work opposed the measures of the secret police with the introduction
of secret agents in the revolutionary area, carried encrypted correspondence, changed
secret abode. These measures allowed the Union to continue the revolutionary activities
against monarchal regime.